Traditional Food Entrepreneurs in Sabah and Selangor States: A qualitative perspective - Adilah Md Ramli; Mazni Saad; Mohd Shazali Md Shariff; Joko Sulistyo (ResearchGate, 2023)
This study aimed to explore local entrepreneurs during the COVID-19 pandemic in Sabah and Selangor states. Twenty participants from the selected business categories were identified and interviewed using a semi-structured question. Two themes: Food category (coded: categories of food; type of food) and Business criteria (coded: experience, customer, type of business). Entrepreneurs from both states adapt to the changes due to the COVID-19 pandemic by implementing new methods to sustain their business, customer, and type of business. The concerned entrepreneurs must adapt to the changes due to the COVID-19 pandemic by implementing new methods to sustain their business life.